STRUCTURAL CHANGES IN GRAIN GROWING IN SAMARKAND REGION: AN ANALYSIS OF THE GROWTH OF FARMS AND DECREASE IN THE SHARE OF PEHKAN FARMS (ON THE EXAMPLE OF 2019-2020) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article is devoted to the analysis of the dynamics of grain production in Samarkand region for 2019-2020. On the basis of comparative analysis of official statistical data, changes in production volumes (in tons) and growth rates (%) by economic categories (farms, peasant farms, agricultural enterprises) and administrative territories (cities and districts) have been studied. The results of the analysis showed an increase in the total grain production (13.1%) during this period, mainly due to a significant increase in the share of farms (17.4%). On the contrary, there was a sharp decrease in the share of peasant farms (19.7%), while a moderate (15.7%) growth was observed in agricultural enterprises. The analysis also revealed significant inter-regional discrepancies: some districts recorded very high growth rates, while in other regions, production declined. The results indicate that the region is undergoing a structural shift towards larger farms in the grain growing sector and underscore the need for a differentiated agrarian policy, taking into account the divergent trends by farm categories and regions.